Estimated Cost to a Restaurant of a Foodborne Illness Outbreak. (May 2018) - Bartsch, Sarah M.; Asti, Lindsey; Nyathi, Sindiso; Spiker, Marie L.; Lee, Bruce Y.
Objectives: Although outbreaks of restaurant-associated foodborne illness occur periodically and make the news, a restaurant may not be aware of the cost of an outbreak. We estimated this cost under varying circumstances. Methods: We developed a computational simulation model; scenarios varied outbreak size (5 to 250 people affected), pathogen (n = 15), type of dining establishment (fast food, fast casual, casual dining, and fine dining), lost revenue (ie, meals lost per illness), cost of lawsuits and legal fees, fines, and insurance premium increases. Results: We estimated that the cost of a single foodborne illness outbreak ranged from $3968 to $1.9 million for a fast-food restaurant, $6330 to $2.1 million for a fast-casual restaurant, $8030 to $2.2 million for a casual-dining restaurant, and $8273 to $2.6 million for a fine-dining restaurant, varying from a 5-person outbreak, with no lost revenue, lawsuits, legal fees, or fines, to a 250-person outbreak, with high lost revenue (100 meals lost per illness), and a high amount of lawsuits and legal fees ($1 656 569) and fines ($100 000). This cost amounts to 10% to 5790% of a restaurant's annual marketing costs and 0.3% to 101% of annual profits and revenue. The biggest cost drivers were lawsuits and legal fees, outbreak size, and lost revenue. Pathogen type affected the cost by a maximum of $337 000, the difference between a Bacillus cereus outbreak (least costly) and a listeria outbreak (most costly). Conclusions: The cost of a single foodborne illness outbreak to a restaurant can be substantial and outweigh the typical costs of prevention and control measures. Our study can help decision makers determine investment and motivate research for infection-control measures in restaurant settings.